FACTORS RELATING TO THE COMPLETENESS OF DOCUMENTATION CONTENT USING ELECTRONIC MEDICAL RECORDS IN THE EMERGENCY DEPARTMENTS OF TAMAN HUSADA HOSPITAL BONTANG - Sri Ariyani; Wiyadi Wiyadi; Ratanto Ratanto (Bajang Institute, 2023)
Introduction: Medical records are one of the standards for improving the quality of hospital medical services (Ministry of Health, 2008b). Implementation of electronic medical records in the emergency room at Taman Husada Bontang Regional Hospital began in November 2019 without any SOP (Standard Operating Procedure) or technical guidelines for filling out electronic medical records. , so that many electronic medical records are found to be incompletely filled out. Method: This type of quantitative research uses a cross sectional approach, with descriptive observational research methods. The sample in this study consisted of 26 respondents (total sampling), with a non-probability sampling technique. The instrument used was the workload questionnaire by Nursalam (2017). Meanwhile, the questionnaire for the level of knowledge and infrastructure uses a questionnaire that has been tested for validity and reliability. Results: The results of the chi square test showed a significant p value <0.005, namely the relationship between workload and completeness of documentation content (p value 0.001) and the relationship between workload and level of knowledge (p value 0.001).